DUALISME KEWENANGAN PADA PELAYANAN PERTANAHAN DI KOTA BATAM TAHUN 2018 - Prayetno Tri Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The dualism of authority in land services in Batam City, this is the Batam Authority (OB) now the Batam Concession Agency (BP) with Presidential Decree Number 41 of 1973 concerning the Batam Island Industrial Area and Decree of the Minister of Home Affairs Number 43 of 1977 concerning Management and Use of Land in The Batam Island Industrial Area provides authority to BP Batam in the land sector. The birth of the Batam City Government as stipulated in Law Number 53 of 1999 concerning the Establishment of Pelalawan Regency, Rokan Hulu Regency, Rokan Hilir Regency, Siak Regency, Karimun Regency, Natuna Regency, Kuantan Singingi Regency, and Batam City made Batam City an autonomous region that has mandatory affairs authority in the land sector. The purpose of this study is to describe the Dualism of Authority in Land Services in Batam City in 2018.This research uses a qualitative approach. This type of research is descriptive. The research location is in Batam City. Types and sources of data are divided into primary data with informant retrieval techniques through observations of researchers and secondary data in the form of supporting data related to dualism of authority in land services. Data collection techniques used by interviews and documentation. Meanwhile, data analysis was carried out using qualitative analysis.            The results show that the Dualism of Authority in Land Services in Batam City in 2018. In this case the Batam Authority (BP Batam) has the authority to manage land rights in Batam City, the Batam City Government does not have the authority in the land sector. The dualism of authority between the Batam Concession Agency and the Batam City Government is in legal uncertainty which causes frequent changes in policies that cause potential investors to hesitate to invest in Batam City. This has an impact on economic growth in Batam City.Keywords: Dualism of Authority, Land Services, Batam City